Critères pour apprécier les difficultés d’accès à l’indemnisation des travailleurs immigrants victimes de lésions professionnelles - Sylvie Gravel; Jean-Marc Brodeur; François Champagne; Katherine Lippel; Louis Patry; Laurence Boucheron; Michel Fournier; Bilkis Vissandjée (Perspectives Interdisciplinaires sur le Travail et la Santé)
As a general rule, almost all of Quebec’s workers who suffer work injuries will be taken care of by the worker compensation system. However, access to worker compensation is difficult for many workers, including immigrant workers. This article describes the evaluation process and the criteria used for assessing the difficulties encountered by workers during the compensation process. Three groups of experts assigned difficulty scores to a sample group from the Montreal region consisting of 104 immigrant and non-immigrant musculoskeletal injury victims. The difficulty scores were compared using three aspects for evaluation (medical, legal and administrative), which produced the same result: the immigrant workers had higher difficulty scores than the other workers and particularly from the legal and administrative standpoints. The criteria used targeted the human dimensions associated with the lack of understanding during the process and with communication problems in reading documents, completing forms and verbally describing precisely the accident events, the injury circumstances and the medical symptoms.